ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN VARIABLE COSTING PADA UMKM: - Varentz, Hannah; Achmad Fauzi; Prisila Damayanty; Faiza Chairunisa; Nurul Alya Putri; Aleya Safiya; Ainun Nabiilah (Asosiasi Dosen Muda Indonesia, 2023)
This relselarch aims to deltelrminel thel comparativel analysis and calcullation of thel cost of produlction in thel Tahul bulsinelss ulsing fulll costing and variablel costing melthods. This relselarch ulsels qulalitativel melthods wilthsamplels sellelcteld baseld on selcondary data. Selcondary data ils takeln from joulrnal relfelrelncels rellateld to theltiltlel. Analyzel and relport filndilngs relgardilng thel comparilson of thel cost of produlctilon ulsilng fulll costilng andvarilablel costilng melthods of UlMKM, delscrilbel and theln comparel thelm wilth applilcablel theloreltilcal concelpts.Thel relselarch relsullts show that thelrel arel stilll many ovelrhelad costs that havel not beleln ilncluldeld iln thelcalcullatilon of thel cost of produlctilon, thel fulll costilng melthod produlcels thel hilghelst calcullatilon of thel cost ofprodulctilon wheln compareld wilth thel company melthod and thel varilablel costilng melthod.